2020
DOI: 10.3897/mycokeys.67.51133
|View full text |Cite
|
Sign up to set email alerts
|

Gnomoniopsis chinensis (Gnomoniaceae, Diaporthales), a new fungus causing canker of Chinese chestnut in Hebei Province, China

Abstract: Chinese chestnut (Castanea mollissima) is an important crop tree species in China. However, branch canker and fruit rot are two kinds of severe diseases, which weaken the host and decrease chestnut production. During our investigations into chestnut diseases in China, several fungi have been confirmed as casual agents in previous studies, namely Aurantiosacculus castaneae, Cryphonectria neoparasitica, Cry. parasitica, Endothia chinensis and Gnomoniopsis daii. In this study, a new canker pathogen is introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Interestingly, similar symptoms on Castanea mollissima in China were caused by two different species. Gnomoniopsis chinese causes branch canker, and G. daii causes fruit rot [ 54 , 55 ]. In this study, we confirmed the Gnomoniopsis pathogen on leaves in China as G. daii based on the phylogenetic inference of ITS, tef1 and tub2 sequence data ( Figure A10 ), and exactly matched morphology.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, similar symptoms on Castanea mollissima in China were caused by two different species. Gnomoniopsis chinese causes branch canker, and G. daii causes fruit rot [ 54 , 55 ]. In this study, we confirmed the Gnomoniopsis pathogen on leaves in China as G. daii based on the phylogenetic inference of ITS, tef1 and tub2 sequence data ( Figure A10 ), and exactly matched morphology.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, G. smithogilvyi is considered the worldwide most important threat of chestnut fruits, present in Oceania, North America and Europe (EPPO Global database). In China, chestnut rot is caused by other species of Gnomoniopsis , G. chinensis and G. daii (Jiang et al 2020 ; Jiang and Tian 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chinese chestnut (Castanea mollissima Blume) is an important crop/tree species and known as a 'wood cereal-and-oil-yielding' species and an 'iron crop' in China (Jiang, Liang & Tian, 2020). Chestnut kernels are rich in carbohydrates and protein but do not contain gluten or cholesterol, which considered as a healthy food (Chang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%